Falls among Middle-Aged Women in the Women's Interagency HIV Study. Issue 8 (November 2016) - Sharma, Anjali; Hoover, Donald R; Shi, Qiuhu; Holman, Susan; Plankey, Michael W; Wheeler, Amber L; Weber, Kathleen; Floris-Moore, Michelle; Bolivar, Hector H; Vance, David E; Mack, Wendy J; Golub, Elizabeth T; et al.
Background: To determine the frequency and risk factors for falls among middle-aged HIV+ and HIV- women in the Women's Interagency HIV Study (WIHS). Methods: We quantified self-report of any and multiple (≥2) falls in the prior 6 months among 1, 412 HIV+ and 650 HIV- women with mean age 48 years. Logistic regression was used to evaluate associations of demographics, behavioural factors, comorbid conditions and medications with odds of any fall (versus none) and multiple falls (versus ≤1 fall). Results: At least one fall was reported in 263 HIV+ (19%) versus 119 HIV- (18%) women, and ≥2 falls reported in 133 HIV+ (9%) versus 65 HIV- (10%) women. HIV infection was not associated with falls in multivariate analyses. Factors independently associated with any fall included age (adjusted odds ratio [aOR] 1.71, 95% CI 1.17, 2.49 age 50-59 versus <39 years; aOR 2.26, 95% CI 1.38, 3.71 age ≥60 versus <39), current marijuana use (aOR 2.19, 95% CI 1.53, 3.13) depressive symptoms (aOR 1.57, 95% CI 1.21, 2.05 for Center for Epidemiology Studies Depression score ≥16), subjective cognitive complaints (aOR 2.19, 95% CI 1.56, 3.08), neuropathy (aOR 1.59, 95% CI 1.19, 2.13), obesity (aOR 1.39, 95% CI 1.08, 1.80), number of central nervous system active agents (aOR 2.98, 95% CI 1.90, 4.68 for ≥3 agents versus 0) and WIHS site. Factors associated with ≥2 falls included age, marijuana use, number of central nervous system active agents, subjective cognitive complaints, depressive symptoms, neuropathy and study site. Conclusions: Falls were associated with factors affecting cognition, but not HIV status in this large cohort of women. Longitudinal studies are needed to determine the incidence and consequences of falls by HIV status as women age.